Clinical electives at the University of Michigan from the perspective of Ghanaian medical students: A qualitative study - S Danso-Bamfo; N Abedini; H Mäkiharju; K Danso; T Johnson; J Kolars; C Moyer (South African Medical Association, 2017)
Background. Participation in international electives is an integral part of medical training for many medical students, yet little research explores the experiences of students from low-income countries who travel to high-income countries for medical electives.Methods. One hundred and two Ghanaian medical students who participated in 3 - 4-week clinical rotations at the University of Michigan between January 2008 and December 2011 were invited to participate in a mixed-methods study. Face-to-face, semi-structured interviews were conducted with 15 respondents from the larger group who agreed to take part in follow-up interviews. The 60- to 90-minute interviews were audio-recorded and transcribed verbatim, and transcripts were coded by three investigators in an iterative process of thematic identification, codebook generation and revision and consensus discussions.Results. Respondents described perceived differences between Ghana and the USA, including: exposure to ‘new’ aspects of medicine; differences between Ghanaian and US patients, healthcare workers, and patient-provider relationships; and aspects of the US system that they would like to see emulated in Ghana.Conclusion. This preliminary study suggests that international bilateral exchange programmes have lasting value for participants from low-income nations. Further research is needed to determine if the different types of experiences yield measurably different benefits.